3D Multimedia E-Book Based on Mobile Learning Basic Competency of Artistic Hair Coloring - Astuti, Murni; Thaitami, Siti Hajar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The use of appropriate learning media will greatly assist in the learning process. The problem of research is the low understanding of students in the subject of hair trimming and coloring which has an impact on student learning outcomes. The purpose of this study was to develop an e-book-based learning media on the subject matter of double-application hair coloring. This type of research is research and development using a 4-D model. The population of this research is the students totaling 32 people. The data collection technique used a validity and practicality questionnaire. The data analysis technique is by calculating the score of the e-book media assessment from the questionnaire given and categorizing it according to the interpretation obtained. The results of the media validation study were 0.89 (very valid category) and 0.82 material validation (very valid category). The results of the practicality of student responses were 86.07% (very practical category) and from the teacher's response 87.2 (very practical category). E-book-based learning can be said to be valid and practical to be used as teaching materials in the classroom on hair trimming and coloring subjects to improve student learning outcomes.